Proceso atención de enfermería en gestante de 9 semanas con embarazo de alto riesgo asociado a insuficiencia renal crónica etapa 5. - Pariaz Abarca, Nury Elena (2021)
We define pregnancy as a process of changes in the body, on those occasions they turn out to be pathological complications that affect the pregnant woman and the fetus, considering it high risk. When a pregnant woman with a high-risk pregnancy occurs, a complete assessment is started to determine possible situations that in some may be harmful to the pregnant woman and the product. We can include different factors that place a risky pregnancy such as Diabetes Mellitus, Arterial Hypertension, Pre-eclampsia etc. In the following clinical study we will describe the clinical picture of a 9-week pregnant woman associated with Stage V Chronic Renal Insufficiency in the process of dialysis treatment, aiming at the application of the nursing care process being a fundamental tool for the nursing professional who It will allow to assess the lifestyle of the pregnant woman by carrying out a nursing assessment that identifies potential problems and converting them into positive results for the patient by following the therapeutic treatment and reducing the high risk index of the patient with the formation of a detailed care plan. the problems and at the same time resembling them with a Nursing Diagnosis that includes the patient's symptoms, planning the possible results, exposing the necessary interventions for the execution of the same with the expectation of a positive evolution during the hospital stay.